Integrated Dual‐Mode Chromatography to Enrich Extracellular Vesicles from Plasma. Issue 12 (30th April 2020) - Van Deun, Jan; Jo, Ala; Li, Huiyan; Lin, Hsing‐Ying; Weissleder, Ralph; Im, Hyungsoon; Lee, Hakho
Abstract: Purifying extracellular vesicles (EVs) from complex biological fluids is a critical step in analyzing EVs molecularly. Plasma lipoprotein particles (LPPs) are a significant confounding factor as they outnumber EVs >10 4 ‐fold. Given their overlap in size, LPPs cannot be completely removed using standard size‐exclusion chromatography. Density‐based separation of LPPs can be applied but is impractical for routine use in clinical research and practice. Here a new separation approach, known as dual‐mode chromatography (DMC), capable of enriching plasma EVs, and depleting LPPs is reported. DMC conveniently integrates two orthogonal separation steps in a single column device: i) size exclusion to remove high‐density lipoproteins (HDLs) that are smaller than EVs; and ii) cation exchange to clear positively charged ApoB100‐containing LPPs, mostly (very) low‐density lipoproteins (V)LDLs, from negatively charged EVs. The strategy enables DMC to deplete most LPPs (>97% of HDLs and >99% of (V)LDLs) from human plasma, while retaining EVs (>30% of input). Furthermore, the two‐in‐one operation is fast (15 min per sample) and equipment‐free. With abundant LPPs removed, DMC‐prepared samples facilitate EV identification in imaging analyses and improve the accuracy for EV protein analysis. Abstract : Extracellular vesicles (EVs) are a promising source of disease biomarkers. A new, single‐step chromatography approach for EV enrichment, dual‐mode chromatography (DMC) is developed. DMC effectively removes most plasma lipoproteins, >60‐fold more efficient than size‐exclusion chromatography. Consequently, DMC produces an enriched EV population and improves analytical outcomes of EV immunoassays by lowering biological background.